The Influence Of The Work Environment And Organizational Climate On The Work Spirit Of Police Personnel At Lebong Polres Office - Recky Ernando; Ahmad Soleh; Yudi Irawan Abi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of the work environment and organizational climate on the morale of police personnel at the Lebong Police Station. The sample in this study were 53 police personnel at the Lebong Police Station. Data collection techniques using a questionnaire. The analytical method used is multiple regression analysis, hypothesis testing t and hypothesis testing f. The results of multiple linear regression calculations obtained the multiple linear regression equation Y = 5.954 + 0.425X1 + 0.454X2 . The coefficient of determination of the Adjusted R square value is 0.597. This means that X1 (work environment) and X2 (organizational climate) affect work morale (Y) by 59.7% while the remaining 40.3% is influenced by other variables not examined in this study. The results of the F test show that the significance of 0.000 <0.05. Because the significance level below 0.05 indicates that together X1 (work environment) and X2 (organizational climate) have a positive and significant influence on work morale (Y). The work environment has a positive and significant influence on the morale of the police personnel at the Lebong Police Station because of a significant value of 0.000 less than 0.05. 0.05.